Don Lamberton – master academic craftsman: providing the necessary contradiction. (1st December 2015) - Joseph, Richard
Abstract : Don Lamberton's enthusiasm for the study of information economics has played an influential role in many academic careers. This paper searches for those attributes that distinguish Don Lamberton as an influential academic. Lamberton's influence was not solely grounded in the ideas that he promoted; it was also evident in the way he practiced his scholarly craft. The idea of the academic as a master craftsman is developed to explore this important yet often neglected aspect of Don Lamberton's working life. He was a master craftsman who invited and encouraged followers to join with him in a quest to appreciate and understand the role of information in the economy.